2015
DOI: 10.1038/nrneurol.2015.86
|View full text |Cite
|
Sign up to set email alerts
|

Dopa-responsive dystonia—clinical and genetic heterogeneity

Abstract: Dopa-responsive dystonia (DRD) encompasses a group of clinically and genetically heterogeneous disorders that typically manifest as limb-onset, diurnally fluctuating dystonia and exhibit a robust and sustained response to levodopa treatment. Autosomal dominant GTP cyclohydrolase 1 deficiency, also known as Segawa disease, is the most common and best-characterized condition that manifests as DRD, but a similar presentation can be seen with genetic abnormalities that lead to deficiencies in tyrosine hydroxylase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
166
4
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(192 citation statements)
references
References 119 publications
3
166
4
15
Order By: Relevance
“…DRDs typically have dramatic and sustained response to levodopa [12], and their phenotypes are broad [13, 14]. DRD can present with focal, segmental or generalized dystonia in children, or with limb-onset focal or segmental dystonia in adults [13, 14]. The first responsible gene was discovered in 1994 when Ichinose first reported mutations in the GCH1 gene encoding the enzyme GTP cyclohydrolase I [15].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…DRDs typically have dramatic and sustained response to levodopa [12], and their phenotypes are broad [13, 14]. DRD can present with focal, segmental or generalized dystonia in children, or with limb-onset focal or segmental dystonia in adults [13, 14]. The first responsible gene was discovered in 1994 when Ichinose first reported mutations in the GCH1 gene encoding the enzyme GTP cyclohydrolase I [15].…”
Section: Reviewmentioning
confidence: 99%
“…Children with autosomal recessive forms of DRD such as autosomal-recessive GCH1 , TH and SPR mutations may require higher dose (e.g. 6–10 mg/kg/day), as opposed to conventional dose, 4–5 mg/kg/day, in autosomal dominant GCH1 mutations [14, 18]. Exposing patients to high doses (e.g.…”
Section: Reviewmentioning
confidence: 99%
“…1,5 In this autosomal dominant DRD, as BH4 is also the cofactor for TPH, it has been assumed that partial BH4 deficiency results in lowering of serotonin and that there is an increased frequency of nonmotor symptoms relating to a deficit in serotonin. 2,3 However, the present investigation demonstrated that all of the serotonin markers in the striatum were within the control range; we cannot exclude a possibility that even lowdose levodopa treatment might have influenced serotonergic activities (but this influence should be small). Our neurochemical data suggest that the different susceptibility to brain BH4 depletion between TH and TPH could be explained by a difference in the degree of regulatory effects of BH4 on the steady-state level (stability/expression) 1,5 of these 2 hydroxylase proteins.…”
mentioning
confidence: 67%
“…1 Recently, the phenotype of this major form of DRD (GTPCH-deficient DRD) was expanded to include nonmotor symptoms, such as depression, anxiety, and obsessive-compulsive disorder, and these psychiatric symptoms were attributed to serotonin deficiency. 2,3 However, the actual status of brain serotonergic involvement in GTPCH-deficient DRD is unknown. To evaluate possible serotonin deficiency, we measured levels of serotonin markers in the striatum (one of the serotonin-and dopamine-rich brain regions) 4 in a 19-year-old woman with DRD and a GCH1 nonsense mutation.…”
mentioning
confidence: 99%
“…It occurs in different pathological conditions, ranging from dopamine-dependent dystonia [2] to post-stroke deforming spastic hemiparesis [1]. Even though important burden is associated to spastic dystonia, therapeutic options are scarce and mostly limited to intramuscular botulinum toxin injection and surgical partial nerve section.…”
Section: Letter To the Editormentioning
confidence: 99%